Cone beam-computed tomography angiography by intravenous contrast injection is reliable to evaluate patients with large vessel occlusion. (December 2019) - Yamamoto, Nobuaki; Yamamoto, Yuki; Yamaguchi, Izumi; Ishihara, Manabu; Miyamoto, Takeshi; Korai, Masaaki; Shimada, Kenji; Kanematsu, Yasuhisa; Izumi, Yuishin; Takagi, Yasushi
Highlights: Cone beam CTA via intravenous contrast injection might be easy to perform. Cone beam CTA could be reliable to evaluate patients with ELVO. Collaterals on cone beam CTA might be a predictor of prognosis after thrombectomy. Abstract: Purpose: Mechanical thrombectomy (MT) for acute ischemic stroke (AIS) patients due to emergent large vessel occlusion (ELVO) is standard treatment, the benefits, however, are highly time-sensitive. After patient eligibility for reperfusion therapy is determined by conventional radiological examinations, the time to be transferred from the department of radiological examination to angiography-suites is critical. We speculated that the time required for the diagnosis of AIS might be reduced if we could determine MT eligibility in patients with ELVO at angiography-suites. Modern angiography-suites with flat panel detectors can perform cone beam (CB)-CT. We performed CB-CTA using intravenous injection of contrast agent to evaluate occlusion sites, collateral score, and construction of vessels distal to occlusion sites and determined if CB-CTA could be useful to evaluate patients with ELVO. Methods: We included 15 patients with ELVO diagnosed by conventional MRI or CT/CTA, and investigated whether CB-CTA was reliable to diagnose occlusion sites. We also studied if collateral score on CB-CTA was associated with prognosis after successful reperfusion by MT by comparison between favorable (modified Rankin scale (mRS) 0–2), and unfavorable outcome group (mRS 3–6). Results: There was strong agreement of occlusion sites between CB-CTA and conventional radiological examination (κ = 0.80). Collateral score determined by CB-CTA was significantly different between favorable outcome and unfavorable outcome group (median collateral score 2.3 v.s. 1.3, p  = 0.040). Conclusions: Although prospective study of AIS patients at a radiography department is indispensable, CB-CTA performed in an angiography-suite might be useful to evaluate patients with ELVO.